2005
DOI: 10.1111/j.1460-9568.2004.03835.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex plasticity induced by extensive training revealed by transcranial magnetic stimulation in human

Abstract: This study examines the effect of high-level skilled behaviour on motor cortex representations of upper extremity muscles of ten sportswomen. We used transcranial magnetic stimulation to map proximal medial deltoid and distal extensor carpi radialis muscle representations on both hemispheres during low-level voluntary contraction. We compared cortical representation areas between two groups of subjects and between hemispheres within subjects. The first group comprised five elite volleyball attackers and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Our findings are compatible with the occurrence of largescale changes in the functional organization of M1 as a result of sequence or skill learning in humans (Hund-Georgiadis and von Cramon 1999; Karni et al 1995Karni et al , 1998Pascual-Leone et al 1994Tyčè et al 2005) and other mammals (Kleim et al 1998;Plautz et al 2000;Remple et al 2001). Our results are also consistent with recent studies showing marked changes in the properties of a sizable population of M1 neurons as monkeys learn to adapt to new dynamic or kinematic environments (Gandolfo et al 2000;Li et al 2001;Paz et al 2003).…”
Section: Sequence Representation In M1supporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are compatible with the occurrence of largescale changes in the functional organization of M1 as a result of sequence or skill learning in humans (Hund-Georgiadis and von Cramon 1999; Karni et al 1995Karni et al , 1998Pascual-Leone et al 1994Tyčè et al 2005) and other mammals (Kleim et al 1998;Plautz et al 2000;Remple et al 2001). Our results are also consistent with recent studies showing marked changes in the properties of a sizable population of M1 neurons as monkeys learn to adapt to new dynamic or kinematic environments (Gandolfo et al 2000;Li et al 2001;Paz et al 2003).…”
Section: Sequence Representation In M1supporting
confidence: 82%
“…In contrast, the primary motor cortex (M1) is thought to simply produce the patterns of muscle activity necessary to implement the plans generated by the premotor areas. However, results from a number of recent studies suggest that M1 plays a more active role in both the acquisition and retention of motor skills including sequential movements (Hund-Georgiadis and von Cramon 1999; Karni et al 1995Karni et al , 1998Kleim et al 1998;Pascual-Leone et al 1994Plautz et al 2000;Remple et al 2001;Sanes and Donoghue 2000;Tyčè et al 2005). For example, Karni et al (1995Karni et al ( , 1998 reported that practice on a sequence of finger movements resulted in large and lasting increases in the extent of M1 activation.…”
Section: Introductionmentioning
confidence: 99%
“…As skill is acquired at a joint, its trained representation in M1 expands at the expense of neighboring representations (Nudo et al 1996a; Molina-Luna et al 2008; Kleim et al 1998), shifts towards, (Pearce et al 2000; Elbert et al 1995) or shares with (Hlustik et al 2001; Tyc et al 2005) the adjacent untrained representation. Essentially, efficient motor strategy, enhanced input, and acquisition of novel movement sequences create a demand and competition that tips the representational balance in favor of the trained representation (Plautz et al 2000; Pascual-Leone et al 1993, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In primary motor cortex (M1) these changes can be probed with mapping techniques showing excitability changes and representational reorganization associated with extensive motor training [4-6], depending on the nature of movements performed during training [7]. These studies have clinical implications since motor training is known to positively influence motor control in neurological patients [8-11], and novel interventions are emerging that actively alter cortical excitability and might interact with training effects [12].…”
Section: Introductionmentioning
confidence: 99%